SSAU Project of the Nanosatellite SamSat-QB50 for Monitoring the Earth's Thermosphere Parameters. (2015) - Shakhmatov, Evgeniy; Belokonov, Igor; Timbai, Ivan; Ustiugov, Efim; Nikitin, Andrey; Shafran, Stepan
Abstract: SamSat-QB50 nanosatellite design was considered. The main subsystems are described. The basic principles of transformation structure from CubeSat 2U to CubeSat 3U are shown. The passive attitude stabilization system based on hysteresis rods and aerodynamic stabilization principle is suggested for satisfaction of the keys QB50 orientation requirements.